MINAT MASYARAKAT TERHADAP USAHA DELIVERY ORDER PRODUK PERTANIAN DI KOTA BANDA ACEH - Muji Burrahmad; Akhmad Baihaqi; Dimas Sariyanto; Elvira Iskandar (Hasanuddin University, 2020)
One of the marketing strategies in the modern era that offers delivery order facility (delivery service), system implemented at the present time that can help overcome the problem of limited time to buy. This paper aims to identify the level of interest of Banda Aceh city community to the delivery order business of agricultural products, as well as factors related to the interest of the society, and also the most popular type of food agriculture product. This research was conducted in Banda Aceh city, with the object of research of Banda Aceh city society.. The results of this study indicate the interest of Banda Aceh city community to the business of order delivery of agricultural products in high interest category that is with score 30,26. Factors - factors that have a very strong and strong relationship with the interest of the community terahadap delivery business order of agricultural products that is the work, income and accuracy of delivery. Factors that have a weak relationship with the interest of the community to the delivery order of agricultural product is delivery time, distance, price, and information. The type of food that people in Banda Aceh are interested in is food processed products of 65%.